Status Aktivitas FIsik dan Aktivitas Pengalihan Jenuh Mahasiswa di Banyumas selama masa Covid-19 - Ajeng Dian Purnamasari; Izka Sofiyya Wahyurin; Hiya Alfi Rahmah (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
The Covid-19 pandemic has changed the pattern of body movement due to daily activities that do not move much outside the house, especially for students who are affected by the policy of studying from home with online methods that only add time. in front ofthe computer. The purpose of this study was to find out how the condition of the physical activity status of students in the Banyumas Regency area during the Covid-19 pandemic which had lasted more than 1 (one) year in Indonesia (collected all data until April 2021). With a quantitative descriptive method, measuring students' physical activity through recall activities using the International Physical Activities Questionnaire (IPAQ), then calculating the amount of activity time in the Metabolism EquivalentTest (MET) measurement. The number of participants was 329 respondents consisting of students in Banyumas Regency. The results obtained are data on the estimated time to carry out daily activities for 1 week, namely 140 respondents in the inactive category, 111 respondents in the moderate activity category and 78 respondents staying at high activity levels, and 66.75% in activity respondents. to reduce boredom are activities that support sedentary behavior. In conclusion, the findings for respondents are in the form of physical activity numbers that are close to half of the respondents, and the possibility of an increased risk of disease due to lack of movement during the Covid-19 pandemic. Recreational activities were carried out by respondents to support decreased physical activity.